Efecto de la Hipertrigliceridemia experimental en el metabolismo energético del corazón aislado de rata - Carvajal Aguilera, Karla Guadalupe (Universidad Autónoma Metropolitana, 2002)
The metabolic pathways involved in ATP production in hypertriglyceridemic rat hearts were evaluated. Hearts from male Wistar rats with sugar-induced hypertriglyceridemia were perfused in an isolated organ system. Mechanical performance, oxygen uptake and beat rate were evaluated under perfusion with different oxidizable substrates. Age- and weight-matched animals were used as control. The hypertriglyceridemic (HTG) hearts showed a decrease in the mechanical work and slight diminution in the oxygen uptake when perfused with glucose, pyruvate or lactate. No differences viere found when perfused with palmitate, octanoate or P-hydroxybutyrate. The glycolytic flux in HTG hearts was 2.4 times lower than in control hearts. Phosphofructokinase-1 (PFK-1) was 16% decreased in HTG hearts, whereas pyruvate kinase activity did not change. The increased levels of glucose-6-phosphate in HTG heart, suggested a flux limitation by the PFK-1. Pyruvate dehydrogenase in its active form (PDHa) diminished as well. The PDHa level in the HTG hearts was restored to control values by dichloroacetate; however, this addition did not significantly improve the mechanical performance. Levels of ATP and phosphocreatine as well as total creatine kinase activity and the MB fraction were significant lower in the HTG hearts perfused with glucose. The data suggested that supply of ATP by glucose oxidation did not suffice to support cardiac work in the HTG hearts; this impairment was exacerbated by the diminution of the creatine kinase system output. Myocardial performance depends upon the ATP generated through oxidative phosphorylation (OF). To ensure the ATP supply from the production to the consuming sites, the cell utilizes the channelling system of creatine kinase (CK). In the heart of sugar-induced hypertriglyceridemic rat model, cardiac performance is impaired when glucose is the fuel, however, under this condition, it becomes evident that there is an uncoupling between the ATP production, taken as the oxygen uptake in the isolated heart, and the consuming sites, i.e. the mechanical performance in our model. To explore the nature of such uncoupling we evaluated the components of the systems involved. Total CK activity in myocardial tissue was greatly depressed in the HTG hearts. Mitochondrial CK (mitCK) isoenzyme normally correspond to 30% of the total activity found in the whole organ. We determined the corresponding fraction of mitCK taking advantage of the functional coupling existing between the mitCK and the OP; we determined the mitCK activity in isolated heart mitochondria as the stimulation in respiration associated with the ADP generated by mitCK. In the HTG heart mitochondria, the activity of this isoenzyme is depressed by 45% as compared with the values found in control hearts. Adenilate kinase (AK), an enzyme participating in the ATP transfer and ATP / ADP ratio, is slightly, but significantly decreased in the HTG hearts (20% less than in control hearts, P< O.OS). On the other hand, we evaluated heart mitochondrial function from HTG rats. Respiration with 10 mM a-ketoglutarate as oxidizable substrate as well as with 5 mM pyruvate/ mala te (pyr) was significantly larger in HTG heart mitochondria than in the control group (375 ± 32 vs 291±29 ngat O2/min/mg con a-K y 416± 59 vs 288±64 ngat O2/min/mg con pyr). Respiration with l0mM succinate in the presence of 2 µM rotenone were similar in both groups. Quantification of the content of cytocrhomes b, c and a3 showed that they were also similar in the two kinds of mitochondria as well as the cytochrome c oxidase activity. a-ketoglutarate dehydrogenase activity was also measured and was greater in the HTG heart mitochondria than in the control ones: 230±22 vs 180 ± 21 nmol NADH/min/mg prot. Fatty acid composition was determined in mitochondrial membranes. In the HTG heart mitochondria we found a larger content of saturated fatty acids accompanied by a decreased in the content of unsaturated fatty acids. These results indicate that the uncoupling in the energy transfer present in the HTG heart is due mainly to a dysfunction in the mit-CK and AK. Mitochondrial function is preserved in the HTG heart, as reflected in the whole organ, however respiration is augmented when the substrate is a-ketoglutarate since the enzyme responsible far its oxidation is augmented. The change in lipid composition may contribute to increased rigidity, however, further exploration on this matter 1s requiered.; En este trabajo se evaluaron las vías metabólicas responsables de la producción de ATP en corazones de ratas hipertriglicéridemicas (HTG). En un sistema de corazón aislado de acuerdo a la técnica de Langendorff, se determinó el desempeño mecánico, así como el consumo de oxígeno y la frecuencia cardiaca perfundiendo con diferentes sustratos oxidables. Ratas de igual peso y edad fueron utilizadas como controles. Los corazones de ratas HTG tuvieron un menor desempeño mecánico y una discreta disminución en el consumo de oxígeno cuando fueron perfundidos con glucosa, piruvato o lactato. No se encontraron diferencias cuando el sustrato oxidable fue palmitato, octanoato o β-hidroxibutirato. El flujo glucolítico en los corazones HTG fue 2.4 veces menor que en los corazones de ratas control. La actividad de la fosfofructocinasa tipo I (PFKI) disminuyó en un 16% en los corazones HTG con respecto a la actividad presente en corazones control. No se encontraron cambios en la actividad de la piruvato cinasa. Los niveles de glucosa6-fosfato se encontraron elevados en los corazones HTG, sugiriendo una limitación del flujo glucolítico a nivel de la PFKI. La forma activa de la piruvato deshidrogenasa (PDHa) se encontró también disminuida. Sin embargo, mediante la perfusión con dicloroacetato (DCA), se restauró a los valores encontrados en corazones controles, no obstante, este efecto, el desempeño mecánico no se recuperó. Los niveles de ATP y fosfocreatina, así como la actividad de la creatina cinasa total y la fracción MB se encontraron disminuidos en los corazones HTG cuando se perfundieron con glucosa. Los datos sugieren que el suministro de ATP a través de la oxidación de glucosa no es suficiente para mantener el trabajo cardiaco en los corazones HTG, lo cual se agrava por la disminución en la actividad de la creatina cinasa. De la actividad total de CK, un 30% corresponde a la isoforma mitocondrial (CKmit). La actividad de CKmit en corazones HTG está disminuida en un 45%, medida por estimulac1ón de la FO, sin embargo, cuando se cuantificó por espectrofotometría no se encontró diferencia alguna. La adenilato cinasa (AK), enzima que participa también en la transferencia energética y mantenimiento de los niveles celulares de ATP / ADP, se encuentra discreta, pero significativamente disminuida en los corazones HTG (20 % menos que los controles, P< O.OS). La respiración de mitocondrias HTG con a-cetoglutarato (a-K) 10 mM y piruvato/malato (pyr) 5 mM fue significativamente mayor que la de los controles (375 ± 32 vs 291±29 ngát 02/ min/ mg con a-K y 416± 59 vs 288±64 ngát 02/ min/ mg con pyr). Las respiraciones con succinato-rotenona y desacoplada fueron semejantes en mitocondrias HTG y controles. El contenido de citocromos b, c y a fue semejantes para ambos grupos así como la actividad de citocromo C oxidasa. La actividad de a-cetoglutarato deshidrogenasa, fue significativamente elevada en las mitocondrias de corazones HTG: 230±22 vs 180 ±21 nmol N ADH/ min/ mg prot. Se determinó de igual forma la composición de ácidos grasos de membranas mitocondriales. Las mitocondrias HTG mostraron un contenido mayor de ácidos grasos saturados y una disminución de insaturados. Los resultados anteriores indican que el desacoplamiento entre la síntesis de ATP y la actividad contráctil en el corazón HTG se localiza en la transferencia de los equivalentes de energía, principalmente a nivel de la CKmit y de la AK. La función mitocondrial no está alterada en el corazón HTG, tal como se refleja en el corazón intacto, sin embargo parece estar aumentada debido al incremento de a-Kdhasa y posiblemente a un aumento de la rigidez membrana!, aunque esto último debe ser estudiado con mayor profundidad.